Crystallographic evidence for unintended benzisothiazolinone 1‐oxide formation from benzothiazinones through oxidation. Issue 9 (21st August 2020) - Eckhardt, Tamira; Goddard, Richard; Lehmann, Christoph; Richter, Adrian; Sahile, Henok Asfaw; Liu, Rui; Tiwari, Rohit; Oliver, Allen G.; Miller, Marvin J.; Seidel, Rüdiger W.; Imming, Peter
Abstract : X‐ray crystallography revealed the unintended formation of benzisothiazolinone 1‐oxides from 1, 3‐benzothiazin‐4‐ones through oxidation instead of the anticipated benzothiazinone sulfones, which would be constitutional isomers. Abstract : 1, 3‐Benzothiazin‐4‐ones (BTZs) are a promising new class of drugs with activity against Mycobacterium tuberculosis, which have already reached clinical trials. A product obtained in low yield upon treatment of 8‐nitro‐2‐(piperidin‐1‐yl)‐6‐(trifluoromethyl)‐4 H ‐benzothiazin‐4‐one with 3‐chloroperbenzoic acid, in analogy to a literature report describing the formation of sulfoxide and sulfone derived from BTZ043 [Tiwari et al. (2015). ACS Med. Chem. Lett. 6, 128–133], is a ring‐contracted benzisothiazolinone (BIT) 1‐oxide, namely, 7‐nitro‐2‐(piperidine‐1‐carbonyl)‐5‐(trifluoromethyl)benzo[ d ]isothiazol‐3(2 H )‐one 1‐oxide, C14 H12 F3 N3 O5 S, as revealed by X‐ray crystallography. Single‐crystal X‐ray analysis of the oxidation product originally assigned as BTZ043 sulfone provides clear evidence that the structure of the purported BTZ043 sulfone is likewise the corresponding BIT 1‐oxide, namely, 2‐[( S )‐2‐methyl‐1, 4‐dioxa‐8‐azaspiro[4.5]decane‐8‐carbonyl]‐7‐nitro‐5‐(trifluoromethyl)benzo[ d ]isothiazol‐3(2 H )‐one 1‐oxide, C17 H16 F3 N3 O7 S. A possible mechanism for the ring contraction affording the BIT 1‐oxides instead of the anticipated constitutionally isomeric BTZ sulfones and antimycobacterial activities thereof are discussed.